2019
DOI: 10.1016/j.athoracsur.2018.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Customized Cutting Template to Assist Sternotomy in Pectus Arcuatum

Abstract: Purpose. Pectus arcuatum is an anterior chest wall deformity that requires transverse wedge sternotomy. Determining and delivering the correct cutting angle are crucial for successful correction. This report describes the early clinical experience with a novel cutting template technology able to deliver the optimal cutting angle. Description. From patients' computed tomographic scans, the optimal cutting angle is obtained using computer-aided design. A template comprising slots tilted at the right cutting angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…The authors indicated that their method is completely extrapleural and does not need the second operation for plate removal. Leng et al (30) reported total surgical experience of 7 patients with CS syndrome. Authors also used vertical titanium plates along with novel computer-aided design and templates for precise osteotomy angle with a reported excellent cosmetic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The authors indicated that their method is completely extrapleural and does not need the second operation for plate removal. Leng et al (30) reported total surgical experience of 7 patients with CS syndrome. Authors also used vertical titanium plates along with novel computer-aided design and templates for precise osteotomy angle with a reported excellent cosmetic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…3 La tomografía preoperatoria permite conocer la anatomía esternal, así como medir el sitio, ángulo y profundidad del corte esternal, lo que ha permitido el diseño de un molde diseñado de acuerdo con la deformidad esternal, como lo reporta Leng. 9 En esta investigación medimos la longitud y los ángulos de deformidad del esternón en la tomografía y aplicamos estas medidas durante la operación para determinar sitio, ángulo y profundidad de corte. Esto permitió llevar a cabo una corrección adecuada, lo que pudimos corroborar con la tomografía de control, realizada 15 días después de la operación, en donde apreciamos una corrección adecuada del esternón.…”
Section: Discussionunclassified
“…1,3,[6][7][8] Éste se puede calcular mediante placas laterales de tórax, tomografías simples o incluso mediante la creación de modelos virtuales tridimensionales del esternón. 9 El objetivo de este trabajo es mostrar la utilidad de la tomografía de tórax para la planeación de la corrección del pecho arcuato en un paciente pediátrico.…”
Section: Introductionunclassified
“…The names of this deformity include pectus arcuatum, Currarino Silverman syndrome, pouter pigeon chester and chondromal deformation, etc. [3][4][5][6][7][8][9][10][11][12][13] . Different names caused confusion in cognition and treatment of this rare deformity inevitably.…”
Section: Introductionmentioning
confidence: 99%